Dynamics of Islamic Justice during the Kingdom/Sultanate Era in Indonesia - Hendri Hendri; Supardin Supardin; Muh. Rusdi T (al-Wadhih: Journal of Islamic History and Civilization, 2026)
This study aims to examine the dynamics of Islamic judiciary during the kingdom and sultanate era in Indonesia, from the period of Islam's entry to the Dutch colonial era. The method used is library research by analyzing historical sources, legal documents, and relevant academic literature. The results show that Islamic judicial institutions in various Nusantara sultanates had diverse structures and authorities, ranging from courts led directly by the sultan, qadhi, to the council of ulama. Major sultanates such as Aceh, Demak, Mataram Islam, Ternate, and Gowa-Tallo had well-established Islamic judicial systems governing various aspects of community life, including civil, criminal, and religious affairs. The dynamics of Islamic judiciary underwent development and transformation with the arrival of Dutch colonial influence, which gradually restricted the scope of Islamic judicial authority. This research contributes to the understanding of Islamic legal history in Indonesia as part of the Islamic civilization heritage of the Nusantara.